2012
DOI: 10.1007/s10661-012-2960-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-molecular-weight organic acids on kinetics release and fractionation of phosphorus in some calcareous soils of western Iran

Abstract: Organic acid has been related to nutrient mobilization, mainly in phosphorus (P) insoluble utilization, and therefore enhances P bioavailability. In this study, we examined the effect of low-molecular-weight organic acids (malic, citric, and oxalic acids) on P release of some calcareous soils from western Iran. Fractionation and speciation of P in the soil solution were studied at the initial and final P release. Significantly different quantities of P were extracted by the organic acids. On average the maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Hansen and Strawn (2003) reported that the dissolution may be a possible mechanism for Pi release from the well-fitted Elovich model. The power function equation has also been successfully used to describe the kinetics of P released from some calcareous soils induced by LMWOA (Taghipour and Jalali 2013) and P adsorption and desorption Shariatmadari et al 2006). Thus, the increases of Pi and Po release concentration and rate induced by LMWOA (oxalic, citric and malic acids) may be due to the enhancement of P mobilization from the dissolution of soil labile NaHCO 3 -Pi and Po compounds or precipitation of Fe 3+ /Al 3+ -or Ca 2+ -organic acids (Taghipour and Jalali 2013;Wei et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen and Strawn (2003) reported that the dissolution may be a possible mechanism for Pi release from the well-fitted Elovich model. The power function equation has also been successfully used to describe the kinetics of P released from some calcareous soils induced by LMWOA (Taghipour and Jalali 2013) and P adsorption and desorption Shariatmadari et al 2006). Thus, the increases of Pi and Po release concentration and rate induced by LMWOA (oxalic, citric and malic acids) may be due to the enhancement of P mobilization from the dissolution of soil labile NaHCO 3 -Pi and Po compounds or precipitation of Fe 3+ /Al 3+ -or Ca 2+ -organic acids (Taghipour and Jalali 2013;Wei et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The kinetic release of Pi from soils is usually rapid at first, then slows down until an apparent equilibrium is approached (Hansen and Strawn 2003;Jalali and Ahmadi Mohammad Zinli 2011), and the two phases of P release are respectively related to the labile P and less mobile P (Toor and Bahl 1999). Taghipour and Jalali (2013) also suggested that the release of P induced by LMWOA at 10 mmol L -1 was mainly from soil Ca-P (HCl extracted P) fraction, due to the greater chelation of Ca 2+ by organic acids in some calcareous soils of Iran. Further, we hypothesize that (3) citric acid will be most effective in changing soil Fe/Al-Pi and Po fractions while oxalic acid will be most effective in changing Ca-Pi fraction, because of the great affinities of citric acid for Fe/Al and oxalic acid for Ca in soils.…”
mentioning
confidence: 99%
“…1c). When P decreased a certain degree and became the main constraint on tree growth ( Wright et al, 2011), organic acid ( Carvalhais et al, 2011; Taghipour and Jalali , 2013), and extracellular P‐ase ( Shen et al, 2011) excretion by roots increased, and microbial activity ( Richardson et al, 2011) in the rhizosphere soil was enhanced, which strengthened the mobilization of P. Moreover, there were significant ( P < 0.01) correlations between available P and Po in the rhizosphere soil at different developmental stages (Table 4). This means that the level of Po supply (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In both pathways, organic acids preferentially and predominately reduced the P adsorbed on Fe and Al surfaces (Fe-and Al-Pi), rather than associated with Ca (Ca-Pi). This is explained by the fact that organic acid ligands more readily form stable complexes with Fe and Al than Ca (Harrold and Tabatabai 2006) and P is more readily desorbed or dissolved from Fe-and Al-Pi compounds than Ca-Pi compounds (Tiessen et al 1993;Taghipour and Jalali 2013).…”
Section: Discussionmentioning
confidence: 99%